LIGHT RESPONSE OF SHEPHERDIAARGENTEA AND HIPPOPHAE RHAMNOIDES SEEDLINGS UNDER DIFFERENT SOIL MOISTURE CONDITIONS - M. Dong; H. Luo; J. Qin; K. He (Journal of Animal and Plant Sciences, 2015)
In alpine region of Loess Plateau, by using Li-6400 portable photosynthesis system, light response of gas exchange parameters in S. argentea and H. rhamnoides seedlings under different soil moisture conditions was analyzed. The results showed that Pn, Tr and WUE of the two shrub species were both increased with an increase of the PAR. With continued increase of the PAR, Pn and WUE of S. argentea and H. rhamnoides seedlings declined but Tr still increased. With the increase of soil water content (SWC), Pn, Tr of both two shrub species increased, while WUE increased first, then declined after arriving at the maximum under mild water stress condition (W2). When SWC was in the same, light compensation point (LCP) of S. argentea was lower than that of H. rhamnoides obviously, light saturation point (LSP) and efficiency of light energy utilization of S. argentea were higher than those of H. rhamnoides, and the apparent quantum yield (α) in the leaves of S. argentea was higher than that of H. rhamnoides. So compared with H. rhamnoides, photosynthetic capacity of S. argentea was stronger at low PAR. Contrastive analysis indicated that under severe water stress condition (W4)H. rhamnoides was easier to be stressed by high PAR. The capacity utilization ratio of low PAR and WUE in S. argentea was higher than that of H. rhamnoides. Thus, it is concluded that the drought-tolerant productivity of S. argentea seedlings was stronger than that of H. rhamnoides seedlings.
Keywords: net photosynthesis rates; transpiration rate; water use efficiency; light response